2014
DOI: 10.1002/lary.24538
|View full text |Cite
|
Sign up to set email alerts
|

Role of pepsin and pepsinogen: Linking laryngopharyngeal reflux with otitis media with effusion in children

Abstract: 3b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 23 publications
0
44
1
2
Order By: Relevance
“…CXCR4 encodes C-X-C chemokine receptor 4, a member of GPCR receptor family which is found to be overexpressed in many cancer types such as HNSCC. While Luo et al found CXCR4 overexpression to be associated with metastatic LSCC [22], no differences in CXCR4 expression were observed between cancer tissue and counterpart normal tissue in the present study, and no relationship was found with cancer lymph node metastasis. The reason for this discrepancy may be that while both Tan et al [38] and Luo et al [22] found their group of laryngeal cancer samples to contain more lymph node positive samples, 63% of the samples in our group were lymph node negative.…”
Section: Discussioncontrasting
confidence: 96%
“…CXCR4 encodes C-X-C chemokine receptor 4, a member of GPCR receptor family which is found to be overexpressed in many cancer types such as HNSCC. While Luo et al found CXCR4 overexpression to be associated with metastatic LSCC [22], no differences in CXCR4 expression were observed between cancer tissue and counterpart normal tissue in the present study, and no relationship was found with cancer lymph node metastasis. The reason for this discrepancy may be that while both Tan et al [38] and Luo et al [22] found their group of laryngeal cancer samples to contain more lymph node positive samples, 63% of the samples in our group were lymph node negative.…”
Section: Discussioncontrasting
confidence: 96%
“…42,43 Unresponsiveness after PPI treatment in patients with GERD is also associated with poor compliance, psychiatric comorbidities, and functional gastrointestinal disorders. 44,45 After taking PPI, gastric acid secretion is reduced, and the pH in the stomach rises to 4.0 or higher, inhibiting the activation of pepsinogen. 41,46 The current basic principle of drug therapy against GERD is to reduce gastric acid secretion and indirectly reduce the production of pepsin, thereby reducing the amount of gastric acid and pepsin refluxed to the esophagus, throat and other parts, resulting in significantly reduced clinical symptoms and the mucosa damages to the reflux site in GERD patients.…”
Section: Discussionmentioning
confidence: 99%
“…About one-third of children who have pepsin in their middle ear fluid are reported to have abnormal MII-pH investigations [57]. Pepsin and pepsinogen in middle ear effusion are probably caused by laryngopharyngeal reflux and may be involved in the pathogenesis of otitis media [58]. However, little is known about the esophageal reflux symptoms these children do or do not present, the results of reflux tests in those without pepsin in the middle air fluid, the long-term outcome and the impact of reflux therapy.…”
Section: Ger(d) and Other Manifestationsmentioning
confidence: 99%